The Behavioral Sequelae of Cannabis Use in Healthy People: A Systematic Review - Sorkhou, Maryam; Bedder, Rachel H.; George, Tony P. (Frontiers in Psychiatry, 2021)
Background: Cannabis is known to have a broad range of effects on behaviour, including experiencing a “high” and tranquility/relaxation. However, there are several adverse behavioural sequalae that can arise from cannabis use, depending on frequency of use, potency (e.g. THC content), age of onset, and cumulative exposure. This systematic review examined evidence for cannabis-related adverse behavioural sequalae in otherwise healthy human subjects. Methods: Following PRISMA guidelines, we conducted a systematic review of cross-sectional and longitudinal studies from 1990-2020 that identified cannabis-related adverse behavioural outcomes in subjects without psychiatric and medical co-morbidities from PubMed and PsychInfo searches. Key search terms included “cannabis” OR “tetrahydrocannabinol” OR “cannabidiol” OR “marijuana” AND “anxiety” OR “depression” OR “psychosis” OR “schizophrenia” “OR “IQ” OR “memory” OR “attention” OR “impulsivity” OR “cognition” OR “education” OR “occupation. Results: Our search detected a total of 2870 studies, from which we extracted 124 relevant studies from the literature on cannabis effects in the non-clinical population. Effects of cannabis on several behavioural sequelae including cognition, motivation, impulsivity, mood, anxiety, psychosis, and psychosocial functioning were identified. The preponderance of the evidence suggests that frequency of cannabis use, THC (but not CBD) content, age of onset, and cumulative cannabis exposure can all contribute to these adverse outcomes in individuals without a pre-existing medical condition or psychiatric disorder. Conclusions: Although more research is needed to determine risk factors for development of adverse behavioural sequelae of cannabis use, these findings underline the importance of understanding vulnerability to the adverse effects of cannabis, which has implications for prevention and treatment of problematic cannabis use.